Andrea Levy: reivindicative scope in the titles of her novels (Encuentros, 2020)
Andrea Levy was a black British writer with Jamaican roots. This article´s aims focused on standing out reivindications and social denunciation in Levy’s literature, in particular in her titles. By and large, among reivindications we find the making female and black British identity visible which was traditionally ignored in literature. Considering social denunciation, we find this identity social indifference, discrimination and bitter experiences, slavery consequences, identity crisis and the lack of sense of belonging. By observing titles and taking into account analysis of critical theory, we could discover new scopes in interpreting her novels by means of titles. As main conclusion, this article found the visibility of black British female identity in society through literature.